ANALISIS PENCAPAIAN KOMPETENSI SISWA PADA MATA PELAJARAN SHIELDED METAL ARC WELDING DI SMKN 2 KOTA SERANG - Sofian, Muhammad; Putra, Ananda Yhuto Wibisono; Ikhsanudin, Ikhsanudin (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2025)
Vocational High Schools (SMK) aim to produce workers with the technical (hard skills) and non-technical (soft skills) abilities needed to succeed in the era of globalization. Graduates are expected to thrive and compete in the global job market. This study aims to: (1) determine the level of learning achievement in SMAW welding among 12th-grade students at SMKN 2 Kota Serang, (2) analyze the factors influencing SMAW welding competency achievement. This study employs a descriptive qualitative approach with a phenomenological type and data collection techniques including document analysis, observation, and interviews. The data sources in this study were the Head of the Study Program, productive teachers, and 12 students from classes XII TPL 1 and TPL 2. The results of the study indicate that students' competency achievement, particularly in terms of theoretical mastery, is still relatively low. Conversely, students' practical skills showed better results, especially in steel plate welding activities. However, in underhand welding positions according to the Welding Procedure Specification (WPS), both theoretical understanding and practical skills still need to be improved. In terms of visual inspection of welding results, most students have understood the basic theory and are able to identify several types of welding defects, although their understanding of international standards such as ISO 5817 is not yet optimal. Factors influencing competency achievement include the quality of teaching methods, student motivation and discipline, and the availability of practical facilities, particularly limited equipment. Overall, students' competency achievement in SMAW welding is not yet fully optimal and still requires improvement, both in cognitive and psychomotor aspects.